Bakteri PGPR Rizosfer Bambu Sebagai Agens Biokontrol Penyakit Moler: The PGPR Bacteria from Bamboo Rhizosphere as a Biocontrol Agent for Moler Disease - Susanti, Herni; Rianto, Fadjar; Syahputra, Edy (Jurnal Fitopatologi Indonesia, 2025)
The PGPR Bacteria from Bamboo Rhizosphere as a Biocontrol Agent for Moler DiseasePlant growth promoting rhizobacteria are often used as biological agents, either against F. oxysporum or other pathogens. PGPR from bamboo roots have the potential to be used to control Moler disease in shallots. The objective of this study is to evaluate the potential of PGPR from bamboo roots as an antagonist against F. oxysporum. Samples were collected from the rhizosphere of bamboo in different locations in West Kalimantan and isolated using the plating method on nutrient agar. The isolates obtained were tested in vitro as antagonists against F. oxysporum. The results of the test revealed 30 isolates, 19 of which showed inhibition against F. oxysporum. Seven isolates namely isolates PY.01, ST.02, PY.03, S2.05, PR.01, PR.02 and ST.03 were found to produce HCN gas and inhibit F. oxysporum by more than 50%. These isolates were also able to reduce conidia production. Antagonism was also evaluated by the production of metabolites. The antifungal tests of the metabolites of 12 isolates dissolved in the supernatant showed antifungal properties and were able to inhibit the growth of F. oxysporum. The secondary metabolites of isolate PR.01 had the highest inhibition index of 73.08. Isolates ST.02, PR.02 and S2.05 were superior in inhibiting F. oxysporum and produced HCN gas and metabolites.